Simulation of Radio-Frequency Capacitive Discharge at Atmospheric Pressure in Argon - V.Ju. Chebakova (Учёные записки Казанского университета: Серия Физико-математические науки)
A one-dimensional self-consistent model of capacitive coupled radio-frequency discharge between symmetrical electrodes in argon in the local approximation at atmospheric pressure is considered in this paper. Electrons, atomic and molecular ions, metastable atoms and dimers of argon, as well as atoms in the ground state are taken into account in the model. A numerical algorithm is described for solving the mathematical model based on finite-dimensional approximation of the problem using difference schemes with subsequent application of the iterative process for its realization. A software package is developed in the MatLab environment to implement the algorithm of numerical calculation. The results of numerical calculations for the interelectrode distance of 0.2 and 2 cm at atmospheric pressure are given. The results of our calculations are in good agreement with the known results of field experiments and calculations.